Classical singers are also proficient in non-classical singing - Bruder, Camila; Larrouy-Maestri, Pauline (Frontiers in Psychology, 2023)
Classical singers train intensively for many years to achieve a high level of vocal control and specific sound characteristics. However, the actual span of singers’ activities often includes venues other than opera halls and requires performing in styles outside their strict training (e.g., singing pop songs at weddings). We examine classical singers’ ability to adjust their vocal productions to other styles, in relation with their formal training. Twenty-two highly trained female classical singers (aged from 22 to 45 years old; vocal training ranging from 4.5 to 27 years) performed six different melody excerpts a cappella in contrasting ways: as an opera aria, as a pop song and as a lullaby. All melodies were sung both with lyrics and with a /lu/ sound. All productions were acoustically analyzed in terms of seven common acoustic descriptors of voice/singing performances and perceptually evaluated by a total of 50 lay listeners (aged from 21 to 73 years old) who were asked to identify the intended singing style in a forced-choice lab experiment. Acoustic analyses of the 792 performances suggest distinct acoustic profiles, implying that singers were able to produce contrasting sounding performances. Furthermore, the high overall style recognition rate (78.5% Correct Responses, hence CR) confirmed singers’ proficiency in performing in operatic style (86% CR) and their versatility when it comes to lullaby (80% CR) and pop performances (69% CR), albeit with occasional confusion between the latter two. Interestingly, different levels of competence among singers appeared, with versatility (as estimated based on correct recognition in pop/lullaby styles) ranging from 62 to 83% depending on the singer. Importantly, this variability was not linked to formal training per se. Our results indicate that classical singers are versatile, and prompt the need for further investigations to clarify the role of singers’ broader professional and personal experiences in the development of this valuable ability.